The Research on Application of Resistance Compression Network (RCN) in Microwave Rectifying Circuit - Yong Xia; Xiaowei Shi (International Journal of Antennas and Propagation)
Resistance compression networks (RCNs) have attracted special attention in the field of wireless power transmission (WPT) since they were put forward. A lot of research work has been done in rectifier basing on RCN for the purpose of increasing conversion efficiency. It is reported that many kinds of rectifiers containing RCN which operate in various circuit and physical forms are proposed. RCN and all kinds of modified versions are studied deeply in this paper, the rectifiers related to which are analyzed also. The results show that RCN only plays the role of bandpass filter (BPF) in the rectifying circuit, which does not reach the original idea of the first proposer. We have different understandings of the rectifying circuits presented in other papers.